Depths, migration rates and environmental associations of acoustic scattering layers in the Gulf of California. (August 2015) - Cade, David E.; Benoit-Bird, Kelly J.
Abstract: The ecology in the Gulf of California has undergone dramatic changes over the past century, including the emergence of Humboldt squid ( Dosidicus gigas ) as a dominant predator. In the face of these changes, we compare the ubiquitous and ecologically important concentrations of mid-water organisms that comprise acoustic scattering layers to published results, describing their occurrence in detail and showing that they remain similar to features described 50 years previously. To classify scattering layers in the region, we applied an automatic detection algorithm to shipboard echosounder data from four cruises. We consistently detected a broad (>200 m) background layer with a mean daytime bottom boundary depth of 463±56 m (night: 434±66 m), a near-surface layer with mean daytime bottom depth of 43±40 m (night: 61±38 m), and a main migrating layer with mean bottom depth of 333±76 m (night: 54±27 m). Diel vertical migration rates for dusk ascents reached a maximum, on average, of 8.6±3.1 cm s −1, and dawn descents averaged a maximum of 6.9±2.4 cm s −1 . Deep scattering layers were often found concurrent with regions of severe hypoxia and we used environmental data to test for the association of scattering layer boundaries with environmental parameter values. Although results were inconsistent, we found scattering layer depths to be more highly associated with temperature and density than with oxygen. These results suggest that the recent success of D. gigas in the Gulf of California is not likely to be attributable to the effects of shoaling oxygen minimum zones on acoustic scattering layers. Graphical abstract: Highlights: Acoustic scattering layers (SL) in the Gulf of California were identified and measured SL characteristics were similar to 50 years ago, despite dramatic ecosystem changes Layer boundaries were not found to be determined by specific oxygen values A shoaling OMZ is therefore unlikely to determine SL position, size or distribution Recent Dosidicus gigas success in the region is thus likely not due to SL changes